The impact of job satisfaction on valuers’ attitudes towards professional ethics - Agnieszka Małkowska (Vilnius Gediminas Technical University, 2021)
Professional ethics is one of the two pillars of the valuer’s business practice, alongside expert knowledge. Ethical principles are usually formulated within a code of professional ethics which valuers are obliged to follow. The approach to professional ethics is a complex problem and it is conditioned by several factors. In our study, we pose the question whether higher professional satisfaction of real estate valuers translates into more ethical attitudes regarding work-related dilemmas. We conducted research on property valuation services in two European markets: Austria and Poland. Data for the analysis was drawn from 176 surveys in which valuers were asked to respond to hypothetical work situations corresponding to the principles of the real estate valuer’s code. The results obtained using the ordinary least squares (OLS) and two-stage last squares (2SLS) regression methods allow us to conclude that higher job satisfaction positively impacts valuers’ ethical attitudes. The segment of the market served is also an important driver. Valuers who mainly work for property developers show a significantly lower level of ethical attitudes. The influence of the country on professional ethics is ambiguous.